Impact Of Northern Growth Latitude and Environmental Factors on Tocopherols and Phenolic Compounds In Sea Buckthorn (Hippophaë Rhamnoides) Leaves - Iboi, Osagie (My University, 2024)
Sea buckthorn leaves contain many health-promoting compounds such as phenolics and tocopherols. The concentration of these compounds is influenced by latitude, harvest time, cultivar, and environmental conditions. This study beams a light on the impact of latitude and environmental conditions on the tocopherol and phenolic content of sea buckthorn leaves of two Finnish cultivars of Terhi and Tytti from Kittilä (north) and Turku (Kakskerta and Paattinen, south) analyzed using UHPLC-FLD and HPLC-DAD respectively. α-Tocopherol was the most dominant of all three tocopherols accounting for 47% of total tocopherols found while contents of γ-tocopherol and δ-tocopherol were 35% and 18%, respectively. Samples cultivated in the south showed a clear discrimination from the samples grown in the North. Samples cultivated in the south had a higher α -tocopherol content (p < 0.05) and vitamin E activity (p < 0.05) when compared to the northern counterparts. The mean tocopherol content in Kittilä was 204.7 ± 13.7 mg/100g DW while Paattinen and Kakskerta had a mean tocopherol content of 264.7 ± 25.7 mg/100g DW and 283.3 ± 14.3 mg/100g DW respectively. The northern samples had a higher δ-tocopherol content of 200.65 ± 13.8 mg/100 g dry weight (DW) when compared to the two growth locations in the south with total average tocopherol content of 108.75 ± 12.4 mg/100 g. Cultivar did not affect the tocopherol concentration of the samples from both locations (p>0.05). The PCA separates the southern and northern samples based on the harvest year. Precipitation and storage time correlated positively with samples from the north with lower levels of tocopherols while temperature correlated positively with samples from the southern location with higher levels of tocopherols. A similar trend was obtained with phenolic content in the southern samples being more prominent than their northern counterparts with rutin and isorhamnetin-3-O-glucoside being the dominant phenolic compounds. The total ellagitannins in Kittilä had a mean concentration of 761.86 ± 61.16 mg/100g DW, the southern location had a mean concentration of 629.23 ± 67.60 for Kakskerta and 772,85±42,72 mg/100g DW for Paattinen. The content of flavonol glycosides in Kittilä was 84.13±11,53 mg/100g DW, while that in Kakskerta was 61,53±6,43 mg/100g DW, and in Paattinen 87.36±9.98 mg/100g DW. PCA showed that the southern samples correlate positively with temperature while the northern samples correlate positively with precipitation. The study reflects the significance of the complexities and roles of latitudinal differences, environmental conditions and storage conditions on the tocopherol and phenolic contents of sea buckthorn leaves.
Keywords: UHPLC-FLD, HPLC-DAD, PCA, Sea buckthorn, Latitude, Tocopherols, Phenolic compounds